The Use of Formulaic Expressions in the Reading Texts of Senior High School Textbooks Grade XI - Wibowo, Yudha Pambudi; Rukmini, Dwi (English Education Journal, 2020)
The present study investigated formulaic expressions in Senior High School textbooks grade XI that are written by non-native speakers. The objectives of this study are (1) to describe the types of formulaic expressions in the reading texts of grade XI of Senior High School Textbooks (2) to analyze reading texts of grade XI of Senior High School textbooks in order to explain the functions of formulaic expressions, (3) to evaluate reading texts of grade XI of Senior High School textbooks in order to explain the appropriateness of formulaic expressions. The data were taken from reading texts in the English textbooks. The units of analysis were major and minor clauses that contain formulaic expressions. The main category of formulaic expressions was based on Biber, Johansson, Leech, Conrad, and Finegan’s (1999) structural category of formulaic expressions. An observation sheet was used as a research instrument. This study showed that (1) not all of lexical bundles variants were fully applied in the reading texts. There were not many examples of idiomatic phrases in the reading texts, (2) formulaic expressions in the reading texts presented various functions, (3) few lexical bundles and free combinations of verb + particles were not appropriately used in the reading texts. The present study revealed that few of formulaic expressions in the reading texts are unnatural. Therefore, the reading texts need improvement. This study offers suggestions especially to the textbook authors regarding the naturalness of formulaic expressions. This study reminds EFL teachers to be more aware of the use of formulaic expressions.